PENGEMBANGAN MOTIF BATIK BERBASIS ILUMINASI NASKAH KUNO MINANGKABAU DALAM PENINGKATAN USAHA RUMAH BATIK DEWI BUSANA DAN CANTING BUANA - Pramono Pramono; Eka Meigalia; Fauzan Misra; M. Yusuf; Rona Almos; Yerri Satria Putra; Bahren Bahren; Nur Ahmad Salman Herbowo (Jurnal Hilirisasi IPTEKS, 2023)
The development and utilization of ancient manuscript illumination need to be done. One of them is designing cloth motifs or batik motifs. The activity was carried out from August to December 2022 with partners Canting Buana Kreatif Padang Panjang and Dewi Busana Pesisir Selatan. The method used is counseling and training. The activity was carried out in six stages. First, preparations include administration, preparation of implementation schedules, licensing processes, and guidelines from August 19 to September 30, 2022. Second, clustered discussions to produce exotic narratives of batik motif designs on October 3 and 4, 2022. Third, batik production training is attended by batik artisans and prospective artisans and students from October 5 to 14, 2022 at Canting Buana Kreatif and Dewi Busana. Fourth, batik production from October 14 to 26, 2022. Fifth, digital marketing training on October 31 and November 1, 2022, at Andalas University. Sixth, an exhibition of batik products produced by the participants will be held from November 3 to December 4, 2022, at the Minangkabau Corner, Andalas University. This activity involves the participation of partners and students. 10 (ten) Students are actively involved in this activity. The benefits of this activity are expected to be the formation of a community ecosystem that is aware of the utilization of cultural heritage (ancient manuscripts) for the creative industry. This activity aims to develop and utilize the treasures of cultural heritage in the form of ancient manuscript illumination treasures for the enrichment of Minangkabau batik motif designs. This activity concludes that artisans from both batik houses and partner participants can develop and understand the philosophy of the motifs for developing Minangkabau ancient manuscript illumination.